Case report: Oxaliplatin-induced idiopathic non-cirrhotic portal hypertension: a case report and literature review - Ye, Jiayuan; Xie, Yilian; Xu, Yaojiang; Chen, Nan; Tu, Yifei (Frontiers in Medicine, 2023)
Oxaliplatin has become a widely used agent in neoadjuvant chemotherapy for gastrointestinal tract tumors and is an integral part of the therapeutic approach for managing colorectal cancer recurrences and metastases, resulting in a more favorable prognosis for patients. Nevertheless, oxaliplatin can give rise to idiopathic non-cirrhotic portal hypertension (INCPH). The emergence of INCPH can disrupt tumor chemotherapy and incite persistent adverse reactions in later stages, significantly complicating clinical management. Consequently, we have presented a case report of INCPH induced by oxaliplatin chemotherapy with the aim of advancing the diagnosis and treatment of this condition, with a particular focus on the clinical manifestations. This study has ascertained that the condition is primarily attributed to complications related to portal hypertension, such as gastrointestinal bleeding, splenomegaly, and hypersplenism. The pathological features primarily involve hepatic sinus dilation and congestion, portal obstruction, absence, stenosis, shunting, localized venous and perisinusoidal fibrosis, as well as hepatocellular atrophy. Treatment primarily concentrates on strategies typically employed for cirrhosis. Endoscopic ligation, sclerotherapy, and non-selective beta-blockers (NSBBs) can be selected to prevent and treat variceal hemorrhage. Transjugular intrahepatic portosystemic shunt(TIPS)and liver transplantation can also be chosen for severe cases. Notably, despite the timely discontinuation of oxaliplatin, most patients continue to experience disease progression, This is a provisional file, not the final typeset article ultimately resulting in a poor prognosis due to either tumor advancement or the ongoing progression of portal hypertension. This emphasizes the importance for physicians to be aware of and consider the risk of INCPH when prescribing oxaliplatin.